Pharmacogenomic Analysis in Determining Optimal Drug Dosage in Chronic Disease Patients in Indonesia - Rosmerry Simanjuntak; Henny Sutrisman; Adrianus Prihartanto; Rossa Ramadhona (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
. Pharmacogenomics, the science that combines genetics with pharmacology, plays a vital role in determining the optimal dosage of drugs for patients, especially those with chronic diseases. In Indonesia, the use of pharmacogenomic approaches is still limited even though the genetically diverse population requires more personalized dosage adjustments. This study aims to analyze the effect of genetic variation on drug response in patients with chronic diseases, such as diabetes, hypertension, and cardiovascular disease, in Indonesia. By collecting and analyzing genetic data and patient clinical data, this study will identify genetic biomarkers associated with drug metabolism and therapeutic effectiveness. The results of this study are expected to provide guidance for more accurate and personalized drug dosage determination, which will ultimately improve therapeutic outcomes and reduce the risk of side effects. This study is also expected to encourage wider adoption of pharmacogenomic approaches in clinical practice in Indonesia, as part of the effort towards more personalized and effective medicine.